2021
DOI: 10.1002/jcc.26516
|View full text |Cite
|
Sign up to set email alerts
|

Generalized–ensemble method study: A helix‐mimetic compound inhibits protein–protein interaction by long‐range and short‐range intermolecular interactions

Abstract: A heterocyclic compound mS-11 is a helix-mimetic designed to inhibit binding of an intrinsic disordered protein neural restrictive silence factor/repressor element 1 silencing factor (NRSF/REST) to a receptor protein mSin3B. We apply a generalized ensemble method, multi-dimensional virtual-system coupled molecular dynamics developed by ourselves recently, to a system consisting of mS-11 and mSin3B, and obtain a thermally equilibrated distribution, which is comprised of the bound and unbound states extensively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 89 publications
(157 reference statements)
0
9
0
Order By: Relevance
“…It also ameliorates social interaction deficits in a prenatal valproic acid-induced autism mouse model . Detailed in silico analysis by enhanced molecular dynamics simulation revealed that this scaffold induced PPI inhibition by long-range molecular orientation ordering followed by short-range interactions …”
Section: Introductionmentioning
confidence: 98%
“…It also ameliorates social interaction deficits in a prenatal valproic acid-induced autism mouse model . Detailed in silico analysis by enhanced molecular dynamics simulation revealed that this scaffold induced PPI inhibition by long-range molecular orientation ordering followed by short-range interactions …”
Section: Introductionmentioning
confidence: 98%
“…First, we briefly explain this method, which provides a conformational ensemble of the system and a thermodynamic weight at the simulation temperature 𝑇 ( 300 K in the present study), which is assigned to conformations stored in the ensemble. Details of GA-mD-VcMD have been explained elsewhere 13,14,15,16 . Next, we explain the molecular system which consists of hETB, bosentan, membrane (cholesterol and POPC lipid molecules), and solvent (water molecules and ions).…”
Section: Methodsmentioning
confidence: 99%
“…We applied this method to some biological systems, which consist of a protein and ligand in an explicit solvent 14,15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…First, we briefly explain this method, which provides a conformational ensemble of the system and a thermodynamic weight at the simulation temperature 𝑇 ( 300 K in the present study), which is assigned to conformations stored in the ensemble. Details of GA-mD-VcMD have been explained elsewhere 13,14,15,16 . Next, we explain the molecular system which consists of hETB, bosentan, membrane (cholesterol and POPC lipid molecules), and solvent (water molecules and ions).…”
Section: Methodsmentioning
confidence: 99%
“…To overcome this difficulty, we introduced a GA-guided multi-dimensional virtual-system coupled molecular dynamics method (GA-mD-VcMD) 13 , which is an extension of the original mD-VcMD, where "GA" is an abbreviation of genetic algorithm. We applied this method to some biological systems, which consist of a protein and ligand in an explicit solvent 14,15,16 .…”
Section: Introductionmentioning
confidence: 99%